Polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane and preparation method and application thereof

By crosslinking modified polybenzimidazoles containing long alkyl side chain ion conduction groups with polyaralkyl polymers with halogenated alkyl side chains, a high-performance anion exchange membrane is designed, which solves the problem of poor chemical stability of the anion exchange membrane in an alkaline environment, and achieves the improvement of high ion conductivity and mechanical properties.

CN118978729BActive Publication Date: 2025-04-22QINGDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411046974.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2025-04-22
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

The existing anion exchange membranes have poor chemical stability in alkaline environments, resulting in reduced ionic conductivity and rapid degradation of cationic groups.

Method used

By crosslinking modified polybenzimidazoles containing long alkyl side chain ion conduction groups with polyaralkyl polymers with halogenated alkyl side chains, a high-performance anion exchange membrane with a clear/hydrophobic microphase separation structure was designed.

Benefits of technology

It improves the ion conductivity and mechanical properties of the anion exchange membrane, enhances the chemical stability in an alkaline environment, and is suitable for anion exchange membrane water electrolytic cells and alkaline fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978729B_ABST
    Figure CN118978729B_ABST
Patent Text Reader

Abstract

This invention discloses a polyarylalkyl crosslinked modified polybenzimidazole anion exchange membrane, its preparation method, and its applications. By crosslinking modified polybenzimidazole with long alkyl side chain ion-conducting groups with a polyarylalkyl polymer having haloalkyl side chains and then casting the mixture, a high-performance anion exchange membrane with a clearly defined hydrophilic / hydrophobic microphase separation structure is designed. The prepared membrane exhibits good dimensional stability and high ionic conductivity, and can be applied in anion exchange membrane water electrolyzers and alkaline fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane, belonging to the technical field of anion exchange membranes. Background Art

[0002] Hydrogen energy technology and application, and hydrogen production from renewable energy are encouraged industries in my country. Among them, hydrogen produced from renewable energy is also called green hydrogen. Compared with traditional hydrogen energy production methods, it achieves zero carbon emissions during the preparation process, so it is also called the purest green energy. Alkaline water hydrogen production is an important way to produce green hydrogen, and anion exchange membrane is one of the core components of alkaline water hydrogen production electrolyzer. The development of anion exchange membranes mainly faces the problems of low ion conductivity and poor mechanical properties. In order to improve conductivity, anion exchange membranes are usually required to have a higher ion exchange capacity (IEC), which can be achieved by increasing the density of ion groups in the membrane, thereby forming an efficient ion transport channel, but this will lead to increased water absorption and swelling of the membrane, thereby reducing the dimensional stability and mechanical properties of the anion exchange membrane. This problem can be solved by cross-linking several polymers with different mechanical properties to form a continuous ion channel. The patent with publication number CN117964932A discloses an interpenetrating network anion exchange membrane of polysulfone cross-linked polybenzimidazole, which is prepared by cross-linking polybenzimidazole (PBI) modified with long alkyl side chain ion conductive groups with modified haloalkyl substituted polysulfone (PSF) material and then casting a film to obtain an anion exchange membrane material with an interpenetrating network structure, thereby improving the dimensional stability and mechanical properties of the anion exchange membrane. However, PSF, as an aryl-ether polymer, is prone to skeleton degradation under alkaline conditions to produce benzyl AEM. Aryl ether cleavage is accelerated by electron traction connection and adjacent cationic groups. In addition, the benzyl position of the cationic group may limit their local mobility, making them particularly susceptible to nucleophilic attack. This fragility can lead to reduced hydroxide conductivity and rapid degradation of cationic groups. Summary of the invention

[0003] The present invention aims to improve the problem of poor chemical stability of existing anion exchange membranes (such as aryl ether polycyclic aromatic hydrocarbon polymers) in alkaline environments, and provides a polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane and its preparation method and application. By cross-linking a modified polybenzimidazole (PBI) modified with a long alkyl side chain ion conductive group and a polyarylalkyl polymer with a halide side chain and then casting a membrane, a high-performance anion exchange membrane with a clear hydrophilic / hydrophobic microphase separation structure is designed. The prepared membrane has good dimensional stability and high ion conductivity, and can be used in anion exchange membrane water electrolyzers and alkaline fuel cells.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane, the structure of which is shown below:

[0006]

[0007] Wherein, x and y are positive integers greater than or equal to 1, m is 1 or 2, n is 1, 2 or 3, and Ar is the following structure:

[0008]

[0009] FG + The introduced ion-conducting groups include N-methylalkylpiperidinium ion, trimethylalkylammonium ion, and 1-methyl-3-alkylimidazolium ion.

[0010] A method for preparing a polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane comprises the following steps:

[0011] (1) Preparation of polyarylalkyl polymers

[0012] In an ice-water bath, different aromatic monomers and carbonyl monomers with different chain lengths are added to dichloromethane (DCM) and dissolved and stirred. After the reactants are completely cooled, a superacid is added dropwise, and the ice bath is continued for 10-60 minutes, and the reaction is carried out at room temperature for 2-8 hours. Then, the viscous solution is dropped into a precipitant B to obtain a fibrous solid, which is purified, washed, and dried to synthesize a polyarylalkyl polymer with different side chain lengths;

[0013] (2) Preparation of cross-linked network anion exchange membrane

[0014] The modified polybenzimidazole containing a long alkyl side chain ion-conducting group and the polyarylalkyl polymer obtained in step (1) are dissolved in dimethyl sulfoxide (DMSO) to prepare a casting solution, and the mixture is reacted at 60-80° C., and then the casting solution is cast on a glass plate and dried to form a film, and the film is immersed in an alkali solution for ion exchange, and then immersed in deionized water until it becomes neutral, thereby obtaining an anion exchange membrane with a cross-linked network structure.

[0015] The structural formula of the modified polybenzimidazole containing long alkyl side chain ion-conducting groups is:

[0016] X is a halogen atom such as bromine, chlorine, etc.

[0017] The present invention adopts the method described in the patent with publication number CN117964932A to prepare modified polybenzimidazole containing long alkyl side chain ion conductive groups. The specific method is: under nitrogen protection, different nitrogen-containing compounds are dissolved in solvent 1, a certain amount of dibromide is added, and the reaction is carried out at 30-60°C for 12-48 hours, and then filtered and washed with reagent 1 to obtain a white solid. Such white solid is added to a mixed solution of polybenzimidazole and solvent 2 pre-reacted with sodium hydride, and the reaction is carried out at 80°C-100°C for 24-48 hours. The reaction solution is poured into precipitant A, filtered, washed and dried to obtain modified polybenzimidazole modified with long alkyl side chain ion conductive groups.

[0018] The nitrogen-containing compound is N-methylpiperidine, trimethylamine, and 1,2-dimethylimidazole; the dibromide is 1,4-dibromobutane and 1,6-dibromohexane; a certain equivalent of dibromide is 3-5 times the equivalent of dibromide; the amount of white solid added is equivalent to 2-10 times the amount of NH-based substances in polybenzimidazole, wherein 4-6 times is preferred; solvent 1 is tetrahydrofuran, acetone, and acetonitrile; solvent 2 is N,N-dimethylformamide, dimethyl sulfoxide, and N,N-dimethylacetamide; reagent 1 is ether and ethyl acetate; and precipitant A is acetone and water.

[0019] The aromatic monomers described in step (1) are p-terphenyl, biphenyl, biphenyl ether and 9,9-dimethylfluorene, and the structural formulas of p-terphenyl, biphenyl, biphenyl ether and 9,9-dimethylfluorene are specifically as follows:

[0020]

[0021] The carbonyl monomer in step (1) is 6-bromo-1,1,1-trifluorohexane-2-one and 7-bromo-1,1,1-trifluoroheptane-2-one. Of course, the bromine element in the structural formula can also be a halogen element such as chlorine, fluorine, or iodine.

[0022] The superacid in step (1) is trifluoroacetic acid (TFSA) or trifluoromethanesulfonic acid.

[0023] It should be noted that the polyarylalkyl polymers with different side chain lengths are synthesized after purification, washing and drying, specifically, the fibrous solid is redissolved in chloroform, precipitated in precipitant B to obtain a fibrous polymer, repeatedly washed with precipitant B, and finally dried to synthesize the polyarylalkyl polymers with different side chain lengths. The precipitant B is water, methanol, and ethanol.

[0024] The molar ratio of the polyarylalkyl polymer described in step (2) to the modified polybenzimidazole modified with a long alkyl side chain ion-conducting group is in the range of 1:0.5-6.

[0025] The w / v of the casting solution in step (2) is 3-10%.

[0026] In step (2), the modified polybenzimidazole modified with long alkyl side chain ion-conducting groups and the polyarylalkyl polymer are reacted at 60-80° C. for 0.5-3 h.

[0027] The alkali solution described in step (2) is selected from lithium hydroxide solution, sodium hydroxide solution, potassium hydroxide solution, cesium hydroxide solution or barium hydroxide solution, and the concentration range is selected from 0.2mol / L-5mol / L, wherein the alkali solution is preferably sodium hydroxide solution or potassium hydroxide solution, and the concentration is preferably 1mol / L-2mol / L.

[0028] The polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane is used in the fields of fuel cells, water electrolysis electrolyzers, etc.

[0029] The present invention adopts a series of aromatic-free skeletons polymerized by superacid catalysis to replace the previous PSF skeleton. This skeleton has not only higher ionic conductivity but also good alkali stability.

[0030] The beneficial effects of the present invention are as follows: the anion exchange membrane of the polyarylalkyl cross-linked polybenzimidazole has high ion conductivity and excellent mechanical properties and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the conductivity-temperature curve of the cross-linked membrane PTPA-C5-PBI-C6-Pip prepared in the present invention.

[0032] Figure 2 This is the water absorption-temperature curve of the cross-linked membrane PTPA-C5-PBI-C6-Pip prepared in the present invention.

[0033] Figure 3 This is the swelling rate-temperature curve of the cross-linked membrane PTPA-C5-PBI-C6-Pip prepared in the present invention.

[0034] Figure 4 This is the conductivity-time curve (25° C.) of the cross-linked membrane PTPA-C5-PBI-C6-Pip prepared in the present invention after being immersed in 1 M KOH solution.

[0035] Figure 5 The conductivity-time curve (25°C) of the cross-linked membrane PSF-C4-PBI-C6-Pip after being immersed in 1M KOH solution. DETAILED DESCRIPTION

[0036] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0037] Example 1

[0038] (1) Synthesis of modified polybenzimidazoles containing long alkyl side chain ion-conducting groups

[0039] This embodiment adopts the method described in the patent with publication number CN117964932A to prepare polybenzimidazole PBI-C4-Pip, PBI-C6-Pip, PBI-C4-QA, PBI-C6-QA, PBI-C4-Im, PBI-C6-Im modified with long alkyl side chain ion-conducting groups. The specific preparation method is fully cited below.

[0040] (101) Preparation of PBI-C4-Pip:

[0041] Under nitrogen protection, 20mmol N-methylpiperidine was dissolved in acetonitrile, stirred thoroughly, and then 100mmol 1,4-dibromobutane was added, stirred thoroughly, and reacted at 60℃ for 48h. Then the reaction solution was filtered, washed with ether several times, and dried under vacuum at 60℃ for 24h to obtain C4-Pip. 2.5mmol PBI material was dissolved in dimethyl sulfoxide, stirred thoroughly to form a 5wt.% solution, and then 10mmol sodium hydride was added. After reacting at room temperature for 12h, 10mmol C4-Pip was added and reacted at 80℃ for 48h. After the reaction was completed, acetone was used to precipitate, and it was repeatedly washed in acetone for 3-5 times, and dried under vacuum at 60℃ for 24h to obtain PBI-C4-Pip.

[0042] (102) Preparation of PBI-C6-Pip:

[0043] Under nitrogen protection, 20mmol N-methylpiperidine was dissolved in acetonitrile, stirred thoroughly, and then 100mmol 1,6-dibromohexane was added, stirred thoroughly, and reacted at 60℃ for 48h. Then the reaction solution was filtered, washed with ether several times, and dried under vacuum at 60℃ for 24h to obtain C6-Pip. 2.5mmol PBI material was dissolved in dimethyl sulfoxide, stirred thoroughly to form a 5wt.% solution, and then 10mmol sodium hydride was added. After reacting at room temperature for 12h, 10mmol C6-Pip was added and reacted at 80℃ for 48h. After the reaction was completed, acetone was used to precipitate, and it was repeatedly washed in acetone for 3-5 times, and dried under vacuum at 60℃ for 24h to obtain PBI-C6-Pip.

[0044] (103) Preparation of PBI-C4-QA:

[0045] Under nitrogen protection, 20mmol trimethylamine was dissolved in acetonitrile, stirred thoroughly, and then 100mmol 1,4-dibromobutane was added, stirred thoroughly, and reacted at 60℃ for 48h. Then the reaction solution was filtered, washed with ether several times, and dried under vacuum at 40℃ for 24h to obtain C4-QA. 2.5mmol PBI material was dissolved in dimethyl sulfoxide, stirred thoroughly to form a 5wt.% solution, and then 10mmol sodium hydride was added. After reacting at room temperature for 12h, 10mmol C4-QA was added and reacted at a reaction temperature of 100℃ for 24h. After the reaction was completed, it was precipitated with acetone, and repeatedly washed in acetone for 3-5 times, and dried under vacuum at 50℃ for 36h to obtain PBI-C4-QA.

[0046] (104) Preparation of PBI-C6-QA:

[0047] Under nitrogen protection, 20mmol trimethylamine was dissolved in acetonitrile, stirred thoroughly, and then 100mmol 1,6-dibromohexane was added, stirred thoroughly, and reacted at 60℃ for 48h. Then the reaction solution was filtered, washed with ether several times, and dried under vacuum at 40℃ for 24h to obtain C6-QA. 2.5mmol PBI material was dissolved in dimethyl sulfoxide, stirred thoroughly to form a 5wt.% solution, and then 10mmol sodium hydride was added. After reacting at room temperature for 12h, 10mmol C6-QA was added and reacted at a reaction temperature of 100℃ for 24h. After the reaction was completed, it was precipitated with acetone, and repeatedly washed in acetone for 3-5 times, and dried under vacuum at 50℃ for 36h to obtain PBI-C6-QA.

[0048] (105) Preparation of PBI-C4-Im:

[0049] Under nitrogen protection, 20mmol 1,2-dimethylimidazole was dissolved in acetonitrile, stirred thoroughly, and then 100mmol 1,4-dibromobutane was added, stirred thoroughly, and reacted at 60℃ for 48h. Then the reaction solution was filtered, washed with ether several times, and dried under vacuum at 60℃ for 24h to obtain C4-Im. 2.5mmol PBI material was dissolved in dimethyl sulfoxide, stirred thoroughly to form a 5wt.% solution, and then 10mmol sodium hydride was added. After reacting at room temperature for 12h, 10mmol C4-Im was added and reacted at 80℃ for 24h. After the reaction was completed, it was precipitated with acetone, and repeatedly washed in acetone for 3-5 times, and dried under vacuum at 60℃ for 24h to obtain PBI-C4-Im.

[0050] (106) Preparation of PBI-C6-Im:

[0051] Under nitrogen protection, 20mmol 1,2-dimethylimidazole was dissolved in acetonitrile, stirred thoroughly, and then 100mmol 1,6-dibromohexane was added, stirred thoroughly, and reacted at 60℃ for 48h. Then the reaction solution was filtered, washed with ether several times, and dried under vacuum at 60℃ for 24h to obtain C6-Im. 2.5mmol PBI material was dissolved in dimethyl sulfoxide, stirred thoroughly to form a 5wt.% solution, and then 10mmol sodium hydride was added. After reacting at room temperature for 12h, 10mmol C6-Im was added and reacted at 80℃ for 24h. After the reaction was completed, precipitated with acetone, and repeatedly washed in acetone for 3-5 times, and dried under vacuum at 60℃ for 24h to obtain PBI-C6-Im.

[0052] (2) Polyarylalkyl polymers

[0053] In this embodiment, four polyarylalkyl polymers are prepared, namely PTPA-C4, PTPA-C5, PFPA-C4 and PFPA-C5. The specific preparation methods are as follows:

[0054] (201) PTPA-C4 preparation:

[0055] 2mmol of p-terphenyl and 2.2mmol of 6-bromo-1,1,1-trifluorohexane-2-one were added to 5ml of dichloromethane and dissolved and stirred. Then the mixture was placed in an ice bath and stirred for about ten minutes. After the reactants were completely cooled, 1.77ml of TFSA was added dropwise. After an ice bath for 30 minutes, the mixture was reacted at room temperature for 6 hours. Then, the viscous solution was dropped into methanol to obtain a fibrous solid. The polymer was redissolved in chloroform and precipitated in methanol to obtain a fibrous polymer, which was repeatedly washed with methanol and finally dried under vacuum at 60°C for 24 hours to obtain PTPA-C4.

[0056] (202) Preparation of PTPA-C5:

[0057] 2mmol of p-terphenyl and 2.2mmol of 7-bromo-1,1,1-trifluoroheptane-2-one were added to 5ml of dichloromethane and dissolved and stirred. Then the mixture was placed in an ice bath and stirred for about ten minutes. After the reactants were completely cooled, 1.77ml of TFSA was added dropwise. After an ice bath for 30 minutes, the mixture was reacted at room temperature for 6 hours. Then, the viscous solution was dropped into methanol to obtain a fibrous solid. The polymer was redissolved in chloroform and precipitated in methanol to obtain a fibrous polymer. The polymer was repeatedly washed with methanol and finally dried under vacuum at 60°C for 24 hours.

[0058] (203) Preparation of PFPA-C4: 2 mmol of 9,9-dimethylfluorene and 2.2 mmol of 6-bromo-1,1,1-trifluorohexane-2-one were dissolved and stirred in 5 ml of dichloromethane. The mixture was then placed in an ice bath and stirred for about ten minutes. After the reactants were completely cooled, 1.77 ml of TFSA was added dropwise. After an ice bath for 30 min, the mixture was reacted at room temperature for 6 h. The viscous solution was then added dropwise to methanol to obtain a fibrous solid. The polymer was redissolved in chloroform and precipitated in methanol to obtain a fibrous polymer. The polymer was repeatedly washed with methanol and finally dried under vacuum at 60 °C for 24 h to obtain PFPA-C4.

[0059] (204) Preparation of PFPA-C5: 2 mmol of 9,9-dimethylfluorene and 2.2 mmol of 7-bromo-1,1,1-trifluoroheptane-2-one were dissolved and stirred in 5 ml of dichloromethane. The mixture was then placed in an ice bath and stirred for about ten minutes. After the reactants were completely cooled, 1.77 ml of TFSA was added dropwise. After an ice bath for 30 min, the mixture was reacted at room temperature for 6 h. The viscous solution was then added dropwise to methanol to obtain a fibrous solid. The polymer was redissolved in chloroform and precipitated in methanol to obtain a fibrous polymer. The polymer was repeatedly washed with methanol and finally dried under vacuum at 60 °C for 24 h to obtain PFPA-C5.

[0060] (3) Preparation of cross-linked network anion exchange membrane

[0061] The modified polybenzimidazole modified with long alkyl side chain ion-conducting groups prepared in step (1) (PBI-C4-Pip, PBI-C6-Pip, PBI-C4-QA, PBI-C6-QA, PBI-C4-Im and PBI-C6-Im) and the polyarylalkyl polymer (PTPA-C4, PTPA-C5, PFPA-C4 and PFPA-C5) prepared in step (2) are used to prepare a polyarylalkyl cross-linked modified polybenzimidazole interpenetrating network anion exchange membrane.

[0062] The specific preparation method is:

[0063] The modified polybenzimidazole (such as PBI-C4-Pip) modified with long alkyl side chain ion conductive groups prepared above is dissolved in dimethyl sulfoxide. After being fully stirred and dissolved, the prepared polyarylalkyl polymer (such as PTPA-C4) material is continuously added. The molar ratio of the polyarylalkyl polymer to the modified polybenzimidazole modified with long alkyl side chain ion conductive groups is 1:1.2. The mixture is stirred at 80°C for 3 hours. Then, the mixture solution is cast on a clean glass plate, dried at 80°C for 24 hours, the membrane is peeled off from the glass plate, and then the membrane is immersed in 1M KOH for 48 hours, and then immersed in deionized water until neutral to obtain an anion exchange membrane of polyarylalkyl cross-linked polybenzimidazole (such as PTPA-C4-PBI-C4-Pip).

[0064] As shown in Table 1, PBI-C4-Pip was replaced with PBI-C6-Pip, PBI-C4-QA, PBI-C6-QA, PBI-C4-Im or PBI-C6-Im, and PTPA-C4 was replaced with PTPA-C5, PFPA-C4 or PFPA-C5 to prepare different polyarylalkyl cross-linked polybenzimidazole anion exchange membranes.

[0065] Table 1

[0066]

[0067]

[0068] The properties of the corresponding membrane materials are shown in Table 2.

[0069]

[0070]

[0071]

[0072] Among them, the preparation formula of PTPA-C4-PBI-C6-Im is:

[0073]

[0074] Among them, the preparation formula of PTPA-C4-PBI-C4-Im is:

[0075]

[0076] Among them, the preparation formula of PTPA-C4-PBI-C4-Pip is:

[0077]

[0078] Among them, the preparation formula of PTPA-C4-PBI-C6-Pip is:

[0079]

[0080] Among them, the preparation formula of PTPA-C5-PBI-C4-Pip is:

[0081]

[0082] Among them, the preparation formula of PFPA-C5-PBI-C4-Pip is:

[0083]

Claims

1. A polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane, characterized in that: The structure is as follows: Wherein, x and y are positive integers greater than or equal to 1, m is 1 or 2, n is 1, 2 or 3, and Ar is the following structure: FG + The introduced ion-conducting groups include N-methylalkylpiperidinium ion, trimethylalkylammonium ion, and 1-methyl-3-alkylimidazolium ion.

2. A method for preparing the polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane according to claim 1, characterized in that: The following steps are involved: (1) Preparation of polyarylalkyl polymers In an ice-water bath, different aromatic monomers and carbonyl monomers with different chain lengths are added to dichloromethane for dissolution and stirring, and after the reactants are completely cooled, a superacid is added dropwise, and the ice bath is continued for 10-60 minutes, and then the reaction is carried out at room temperature for 2-8 hours, and then the viscous solution is dropped into a precipitant B to obtain a fibrous solid, and after purification, washing and drying, a polyarylalkyl polymer with different side chain lengths is synthesized; (2) Preparation of cross-linked network anion exchange membrane The modified polybenzimidazole containing long alkyl side chain ion-conducting groups and the polyarylalkyl polymer obtained in step (1) are dissolved in dimethyl sulfoxide to prepare a casting solution, and the reaction is carried out at 60-80° C., and then the casting solution is cast on a glass plate and dried to form a film, and the film is immersed in an alkali solution for ion exchange, and then immersed in deionized water until neutral, to obtain an anion exchange membrane with a cross-linked network structure. The structural formula of the modified polybenzimidazole containing long alkyl side chain ion-conducting groups is: X is a halogen atom.

3. The method for preparing the polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane according to claim 2, characterized in that: The structural formula of the aromatic monomer described in step (1) is specifically:

4. The method for preparing the polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane according to claim 2, characterized in that: The carbonyl monomers described in step (1) are 6-bromo-1,1,1-trifluorohexane-2-one and 7-bromo-1,1,1-trifluoroheptane-2-one.

5. The method for preparing the polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane according to claim 2, characterized in that: The superacid in step (1) is trifluoroacetic acid or trifluoromethanesulfonic acid.

6. The method for preparing the polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane according to claim 2, characterized in that: The molar ratio of the polyarylalkyl polymer described in step (2) to the modified polybenzimidazole modified with a long alkyl side chain ion-conducting group is in the range of 1:0.5-6.

7. The method for preparing the polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane according to claim 2, characterized in that: The w / v of the casting solution in step (2) is 3-10%.

8. The method for preparing the polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane according to claim 2, characterized in that: The alkali solution described in step (2) is selected from lithium hydroxide solution, sodium hydroxide solution, potassium hydroxide solution, cesium hydroxide solution or barium hydroxide solution, and the concentration range is selected from 0.2 mol / L-5 mol / L.

9. Application of the polyarylalkyl cross-linked modified polybenzimidazole anion exchange membrane according to claim 1 in the fields of fuel cells and water electrolysis electrolyzers.

Citation Information

Patent Citations

  • Crosslinking type polybiphenyl alkylene anion exchange membrane for fuel cell and preparation method of crosslinking type polybiphenyl alkylene anion exchange membrane

    CN115377466A

  • Polysulfone cross-linked polybenzimidazole interpenetrating network anion exchange membrane as well as preparation method and application thereof

    CN117964932A